2016
DOI: 10.1080/00325481.2016.1210475
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal and macular thickness changes in type 1 diabetes mellitus patients without diabetic retinopathy

Abstract: This study showed that there is choroidal thinning in young Type 1 diabetic patients with early period of disease duration without diabetic retinopathy nor any other systemic diseases. Choroidal changes in type 1 DM seem to begin at nasal and distal temporal retina. These results need to be verified by larger and longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
5
13
0
Order By: Relevance
“…The measurements of PFT and PFV, albeit of secondary importance to our study, appear interesting and require further research in a larger number of eyes. In the present study, pubescent youths with T1D presented with significantly fewer objective signs of retinal and choroidal structure impairment than diabetic adults as previously reported [ 10 13 , 36 38 , 41 ]. We are hoping to continue the follow-up of these young patients to monitor the status of their retinas and choroids.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The measurements of PFT and PFV, albeit of secondary importance to our study, appear interesting and require further research in a larger number of eyes. In the present study, pubescent youths with T1D presented with significantly fewer objective signs of retinal and choroidal structure impairment than diabetic adults as previously reported [ 10 13 , 36 38 , 41 ]. We are hoping to continue the follow-up of these young patients to monitor the status of their retinas and choroids.…”
Section: Discussionsupporting
confidence: 77%
“…Pierro et al found decreased GCC and choroidal thickness only in patients with T2D, not T1D and suggested that insulin resistance might be one of the causes of neurodegeneration [ 41 ]. Most reports reveal that the retina becomes thinner in DR [ 13 , 22 , 40 ]. We confirm these results, as there were significant differences in PFT and PFV between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study as well, we determined that the choroid is thinner in the nasal quadrant in both groups. In a study conducted by Yolcu et al in 60 healthy subjects and 60 type 1 DM patients with no retinopathy, the choroidal thickness was found to become thinner in the subfoveal nasal 1500µm and temporal 1500µm quadrants in type 1 diabetes patients, but no difference was determined between the groups for the other quadrants (13). Querques et al found no difference between the diabetic groups of different stages in terms of change in subfoveal choroidal thickness but reduced subfoveal choroidal thickness in diabetic groups vs the control group (14).…”
Section: Discussionmentioning
confidence: 91%
“…Choroidal thickness (CT) is considered a measure of choroidal blood flow, which supplies the outer retinal layers. Several studies have described the presence of choroidal vasculopathy in diabetic subjects [9,13,14,15,16]. However, those studies—most of which were performed in a paediatric population—have reported contradictory findings, likely due to their small sample sizes.…”
Section: Introductionmentioning
confidence: 99%